Efektivitas Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja dan Prestasi Sekolah Dasar - Harjati, Emi; Anggoro, Subuh (Universitas Negeri Surabaya, 2021)
The principal is an educational leader at the micro-level who carries out management functions, including planning, organizing, mobilizing, and controlling. The objectives of this study are: (1) to analyze the effectiveness of the principal's leadership style in elementary schools (2) to analyze the effectiveness of the principal's leadership style in improving school performance in elementary schools. (3) Analyzing the effectiveness of the principal's leadership style in improving school achievement in elementary schools. The research method used is the survey method. The research subjects were supervisors, principals, and teachers in the Korwilcam Dindik Timur Purwokerto environment, totaling 60 people consisting of 3 supervisors, 15 principals, and 42 classroom teachers. The research instrument is a leadership style questionnaire, school performance, and school achievement planning. The results showed that the principal's leadership style affected performance and achievement in the primary school Korwilcam Dindik Purwokerto Timur by 23.2% (school performance) and 36.2% (school achievement).